A Philosophy of Moderation: The “Center” as an Interpretive Key to the Lao–Zhuang Texts - Rory O’Neill; Riccardo Peruzzi (Religions, 2023)
The “center” is a key concept in early Chinese philosophy. While readings of the Laozi 老子 and Zhuangzi 莊子 often rely on concepts of “nature” and the “natural”, this article proposes the “center” as an interpretive key that informs discussion of contemporary issues while remaining faithful to the core concerns of the texts. While both texts use the “center” to promote a philosophy of moderation, in the Laozi, “holding to the center” (shou zhong 守中) refers to a focus on one’s inner center to counteract the dangers of the external, whereas the Zhuangzi speaks of a centeredness between inner cultivation and outward socialization. In the Laozi, we examine images of one-, two- and three-dimensional centers as well as the bodily practice of focusing on the inner stomach rather than the outward-looking eyes. Our discussion of the Zhuangzi focuses on occupying the “center” (zhongyang 中央) between extreme inward and outward modes of being. The result is a philosophy of moderation that fosters a sense of humility, balance, and impartiality, cautioning against a drive for overreaching solutions for all humanity, and tempering attempts to conform to extreme “naturalness” or reject all “artificiality”.